Factors related to premature loss of deciduous teeth in children 6-10 years of four public schools Puno - 2019 - Cornejo Tito, Siria Yamilet (2021)
Objective: To determine the related factors of the premature loss of deciduous teeth in schoolchildren from poor households. Materials and methods: observational, prospective, cross-sectional and relational study; the estimated population was 1617 schoolchildren of both sexes from 6 to 10 years old with a stratified random sample of 180 children. Approval No. 513-FO-2019 was obtained from the Ethics Committee of the Universidad Católica Santa Maria. In the clinical examination, the index of the International Caries Detection and Control System (ICDAS II), Pulpitis, Ulcer, Fistula, abscess (PUFA-pufa) and diet were evaluated through the Lipari and Andrade questionnaire. The statistical package SSPS version 23 was used, which analyzed the variables in relation to the factors with the student's T tests and chi2. Results: Of the schoolchildren with pulp disease, 82.1% presented premature dental loss, it was found that at older age there is greater loss on average of 79%, the male sex had 86% of dental loss compared to the female 73.4%, therefore, males have a risk factor of 71.7%. Conclusions: pulp pathology is a related factor for premature tooth loss, the parents' decision and choice for tooth extraction as treatment is due to the suppression of dental pain and low financial resources.